The Use of Mind Mapping to Improve the Students’ Writing Ability of Descriptive Texts in the Seventh Grade of SMPN 2 Ngajum Malang - Marsuki Marsuki; Chindy Hanggara Rosa Indah (IKIP Budi Utomo Malang, 2023)
English is an important language used in either formal situation such as class meeting or informal situation such as traveling. Besides, a lot of languages are spoken nowadays, but English is still widely used in the world. The research aims at describing how the mind mapping to improve the students’ ability of descriptive texts in the seventh grade of SMP 2 Ngajum Malang. The research design is a classroom action research conducted to 29 students of the seventh grade at Ngajum Malang as the subject of the study. This research is based on Kurt Lewin's model of CAR, which consists of planning, acting, observing and reflecting. This study was carried out in two cycles, each of which consisted of two meetings. Based on the data analysis, it was found that there was improvement for the students’ writing ability of the descriptive texs after using mind mapping technique. Of thecriteria of success and mastery learning of 75 determined by the school, the students could achieve higher than the score in the cycle 2 of this research. The mean score of students in the preliminary study was 57.58, in cycle 1was 68.6 and in cycle 2 was 79.48. Of the result above, it is concluded that the Use of Mind Mapping could Improve the Students’ Writing Ability of Descriptive Texts in the Seventh Grade of SMPN 2 Ngajum Malang.